2016
DOI: 10.1038/nature17172
|View full text |Cite
|
Sign up to set email alerts
|

Memory retrieval by activating engram cells in mouse models of early Alzheimer’s disease

Abstract: SummaryAlzheimer's disease (AD) is a neurodegenerative disorder characterized by progressive memory decline and subsequent loss of broader cognitive functions 1 . Memory decline in early stages of Alzheimer's is mostly limited to episodic memory, for which the hippocampus (HPC) plays a crucial role 2 . However, it has been uncertain whether the observed amnesia in early stages of Alzheimer's is due to disrupted encoding and consolidation of episodic information, or an impairment in the retrieval of stored memo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
377
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 457 publications
(437 citation statements)
references
References 30 publications
37
377
2
1
Order By: Relevance
“…For instance, it conceptually distinguishes between behavioral amnesia arising from defects in storage and behavioral amnesia arising from defects in recall. It is therefore relevant to recent work showing that a memory engram remains preserved in amnesic mice that do not express contextual fear memory (66,67). Consistent with the framework we present here, in the mouse models of Alzheimer's disease, memory storage largely remains intact, In this illustration, these peaks constitute excitatory and inhibitory engrams, respectively.…”
Section: A Framework For Normal and Variant Memory Storage And Recallsupporting
confidence: 67%
“…For instance, it conceptually distinguishes between behavioral amnesia arising from defects in storage and behavioral amnesia arising from defects in recall. It is therefore relevant to recent work showing that a memory engram remains preserved in amnesic mice that do not express contextual fear memory (66,67). Consistent with the framework we present here, in the mouse models of Alzheimer's disease, memory storage largely remains intact, In this illustration, these peaks constitute excitatory and inhibitory engrams, respectively.…”
Section: A Framework For Normal and Variant Memory Storage And Recallsupporting
confidence: 67%
“…On the other hand, the most common psychoactive drug in the world (caffeine), an adenosine receptor antagonist that boosts neuronal activity, protects against AD (39). Stimulation of the perforant path in an Aβ-based mouse model is sufficient to restore memory retrieval (40). Similarly, transcranial magnetic stimulation in humans increases brain network activity and performance of associative memory, emphasizing the benefit of increased bona fide network activity (41).…”
Section: Discussionmentioning
confidence: 99%
“…But such studies in animals, by demonstrating the malleability of memory, could suggest novel therapeutic strategies. In a mouse model of earlystage Alzheimer's, Tonegawa's group showed that stimulating engram cells in the dentate gyrus can help animals access a memory that once seemed "lost" (11). His laboratory also reduced the effects of negative memories by stimulating neurons associated with a fear engram while introducing male mice to females (a positive experience), suggesting possible future directions for posttraumatic stress disorder and depression research (12).…”
Section: The Substance Of Memorymentioning
confidence: 99%